Identification of Some DNA Damage-Inducible Genes of Mycobacterium tuberculosis: Apparent Lack of Correlation with LexA Binding - Brooks, Patricia C. (American Society for Microbiology, 2001)
The repair of DNA damage is expected to be particularly important to intracellular pathogens such as Mycobacterium tuberculosis, and so it is of interest to examine the response of M. tuberculosis to DNA damage. The expression of recA, a key component in DNA repair and recombination, is induced by DNA damage in M. tuberculosis. In this study, we have analyzed the expression following DNA damage in M. tuberculosis of a number of other genes which are DNA damage inducible in Escherichia coli. While many of these genes were also induced by DNA damage in M. tuberculosis, some were not. In addition, one gene (ruvC) which is not induced by DNA damage in E. coli was induced in M. tuberculosis, a result likely linked to its different transcriptional arrangement in M. tuberculosis. We also searched the sequences upstream of the genes being studied for the mycobacterial SOS box (the binding site for LexA) and assessed LexA binding to potential sites identified. LexA is the repressor protein responsible for regulating expression of these SOS genes in E. coli. However, two of the genes which were DNA damage inducible in M. tuberculosis did not have identifiable sites to which LexA bound. The absence of binding sites for LexA upstream of these genes was confirmed by analysis of LexA binding to overlapping DNA fragments covering a region from 500 bp upstream of the coding sequence to 100 bp within it. Therefore, it appears most likely that an alternative mechanism of gene regulation in response to DNA damage exists in M. tuberculosis.